Analysis of Factors Affecting Customer Satisfaction in Subsidized Housing in Payakumbuh City - Indra Poetoet Cahyadi (Enrichment : Journal of Management, 2022)
In a business world that is developing towards consumer centricity, customer satisfaction is a very strategic matter and is a major consideration. Because this affects the future sustainability of a company. Not only cultivating profits, maintaining consumers is an absolute thing to manage a good relationship with the company. The amount of competition among housing developers requires developers to focus more on providing competitive advantages in providing services to their housing consumers. Market research in the property business, customer satisfaction is very important and crucial to be able to find out the extent of consumer satisfaction in housing and the property business. This study aims to measure consumer satisfaction as residents of subsidized housing built in 2017. These consumers are in 2 (two) Subsidized housing locations in Payakumbuh City, based on 4 (four) factors namely location, Building Quality, facilities and infrastructure, and utilities. The sampling technique used was purposive sampling and the survey method used in data collection was by distributing questionnaires directly to respondents. The results showed that residents were satisfied with the variable quality of buildings, facilities and infrastructure. However, the results of the analysis of location and utility show differences in satisfaction.